2010
DOI: 10.1038/eye.2010.125
|View full text |Cite
|
Sign up to set email alerts
|

Urine catecholamine levels as diagnostic markers for neuroblastoma in a defined population: implications for ophthalmic practice

Abstract: Purpose Although elevated urinary catecholamine levels have been reported in 90–95% of patients with neuroblastoma, more recent studies of pediatric Horner syndrome caused by an underling neuroblastoma have reported normal values at presentation. The purpose of this population-based study is to report the percentage of cases of neuroblastoma with elevated urinary catecholamine levels at presentation and to suggest a recommended work-up for cases of idiopathic pediatric Horner syndrome. Methods The medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…1, some aldehyde compounds in the body are not stable and transformed to others quickly, just the 14 kinds of CAs can be measured; so, the quantitation of the 14 kinds of CAs concentrations in biological specimens is useful as an index for several diseases, for example, Alzheimer's disease, [5][6][7] hypertension, [8,9] pheochromocytoma [10,11] and neuroblastoma. [4,12,13] Several reports have illustrated that the level of CAs and their metabolites in body fluids is different between normal people and patients with Alzheimer's disease (AD). [5,14] Collecting cerebrospinal fluid or plasma can be invasive, so urine may be a good selection.…”
Section: Introductionmentioning
confidence: 99%
“…1, some aldehyde compounds in the body are not stable and transformed to others quickly, just the 14 kinds of CAs can be measured; so, the quantitation of the 14 kinds of CAs concentrations in biological specimens is useful as an index for several diseases, for example, Alzheimer's disease, [5][6][7] hypertension, [8,9] pheochromocytoma [10,11] and neuroblastoma. [4,12,13] Several reports have illustrated that the level of CAs and their metabolites in body fluids is different between normal people and patients with Alzheimer's disease (AD). [5,14] Collecting cerebrospinal fluid or plasma can be invasive, so urine may be a good selection.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Sharp found that urinary VMA was elevated in 63% of the tested children and 60% of patients have metastatic disease. [16] Berthold et al…”
Section: Discussionmentioning
confidence: 97%
“…However, because urine catecholamine studies have been normal in a few children with neuroblastoma, as in our patient, further investigations are often needed to exclude tumoral lesion. 15 Finally, metaiodobenzylguanidine scintigraphy is out of the initial radiological approach. Nevertheless, it is an interesting technique to characterize the nature of a neck or chest mass in pediatric population when neuroblastoma is suspected.…”
Section: Other Investigationsmentioning
confidence: 99%